Literature Review: Correlation Between Exclusive Breastfeeding and Incident of Diarrhea to Toddlers - Kili Astarani; Dewi Ika Sari Hari Poernomo; Cindy Nova (STIKes Patria Husada Blitar, 2022)
Exclusive breastfeeding is giving ASI without other additional food to infants aged 0-6 months. Babies are not given anything to eat, except food directly produced by the mother because the baby gets the best nutrition through breast milk. Although the efficacy of breast milk is so great, but not many mothers are willing or willing to give exclusive breastfeeding for 6 months as suggested by the world health organization. In Kediri Baptist Hospital, most toddlers do not get exclusive breastfeeding. The objective of this study is to analyze the relationship between exclusive breastfeeding and the incidence of diarrhea to toddlers based on the results of a literature review. This research used Literature review. Literature was obtained using Google Scholar and DOAJ (Directory of Open Access Journals). The results of research on exclusive breastfeeding was according to Sing, et al. (2018) 54.1%, according to Analinta, (2019) 69.2%, according to Sinaga, et al. (2018) 55.9%, according to Rini, (2018) 37.5%, according to Tamimi, (2016) 46.3%, according to Istiqamah, et al. (2013) 56.2%, and the incidence of diarrhea according to Sing et al. (2018) 68.4%, according to Analinta, (2019) 59%, according to Sinaga, et al. (2018) 27.5%, according to Rini, (2018) 59.4%, according to Tamimi, (2016) 19.5%, Istiqamah, et al. (2013) 40.6%. It was concluded that Correlation Between Exclusive Breastfeeding and Incident of Diarrhea to Toddlers.